The emergency service volunteer management framework - McGill, C.; Pidgeon, J.; Gagné, Marylène (2019)
© 2020, Australian Institute for Disaster Resilience. Current high turnover rates among emergency services volunteers are concerning given the pivotal role they play in emergency services organisations. Each 'lost' volunteer reflects a loss of valuable skills and experience on top of the financial loss associated with training.